2008
DOI: 10.1002/art.23732
|View full text |Cite
|
Sign up to set email alerts
|

Ocrelizumab, a humanized anti‐CD20 monoclonal antibody, in the treatment of patients with rheumatoid arthritis: A phase I/II randomized, blinded, placebo‐controlled, dose‐ranging study

Abstract: Objective. Ocrelizumab, a humanized anti-CD20 monoclonal antibody, was studied in a first-in-human trial in rheumatoid arthritis (RA) patients receiving concomitant methotrexate (MTX).Methods. The ACTION trial was a combined phase I/II study of placebo plus MTX versus ocrelizumab plus MTX in 237 RA patients (intent-to-treat population). During phase I, 45 patients were treated with 1 of 5 escalating doses of study drug (infusions on days 1 and 15, 10-1,000 mg per each infusion). An additional 192 patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(129 citation statements)
references
References 18 publications
6
120
0
3
Order By: Relevance
“…[33][34][35] Most 2 nd generation antibodies have pursued doses close to or higher than the 375 mg/m 2 dose typically given with rituximab. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] However, a proper doseranging study has never been reported even though the initial studies of rituximab in non-Hodgkin's lymphoma had demonstrated that treatment responses could also occur at much lower doses. 36,37 In other diseases like immune thrombocytopenia (ITP), with presumably less antigen burden, 100 mg rituximab doses have shown activity, 38 and even in the face of the high leukemic burden in chronic lymphocytic leukemia, frequently repeated 20 mg subcutaneous rituximab doses given to 4 patients were shown to be active in one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35] Most 2 nd generation antibodies have pursued doses close to or higher than the 375 mg/m 2 dose typically given with rituximab. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] However, a proper doseranging study has never been reported even though the initial studies of rituximab in non-Hodgkin's lymphoma had demonstrated that treatment responses could also occur at much lower doses. 36,37 In other diseases like immune thrombocytopenia (ITP), with presumably less antigen burden, 100 mg rituximab doses have shown activity, 38 and even in the face of the high leukemic burden in chronic lymphocytic leukemia, frequently repeated 20 mg subcutaneous rituximab doses given to 4 patients were shown to be active in one.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22] Veltuzumab (hA20) is a humanized, anti-CD20 MAb with similarities as well as structural and functional differences from rituximab. [23][24][25][26] In the complementarity-determining regions, veltuzumab differs from rituximab by only one amino acid, but has completely different framework regions.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to rituximab, ocrelizumab binds to a different but overlapping epitope of the extracellular domain of CD20 [37]. As compared to rituximab, ocrelizumab is associated with increased antibody-dependent cell-mediated cytotoxicity and reduced complement-dependent cytotoxic effects in vitro, which is postulated to make ocrelizumab a more effective drug by modulating tissue-dependent mechanisms of pathogenic response [38].…”
Section: Ocrelizumabmentioning
confidence: 99%
“…Some of these serious infections resulted in death. Even though initial trials in RA were promising [37], the manufacturing companies, Biogen Idec (Weston, MA) and Roche (Basel, Switzerland) on its development in RA due to a lack of improvement in the efficacy and safety of ocrelizumab compared with rituximab in RA and lupus nephritis [39].…”
Section: Clinical Safety and Tolerabilitymentioning
confidence: 99%
“…Rituximab, a chimeric anti-CD20 monoclonal antibody has the ability to deplete B-cells by multiple mechanisms and results are encouraging when it was tried against a variety of autoimmune disorders (Wylam et al, 2003;Ruegg et al, 2004;Stuve et al, 2005).. In extension ocrelizumab, a humanized version of rituximab is currently in the developing stage for targeting several autoimmune disorders (Genovese et al, 2008). The same also holds true for Epratuzumab, a humanised mab that acts by blocking CD22 and GAD-Glutamicacid decarboxylase; NAchR-Nicotinic acetylcholine receptors; VGCC-Voltage gated calcium channels; VGKC-Voltage gated potassium channels thereby depletes B-cell population (Dalakas, 2008).…”
Section: What's In the Pipeline?mentioning
confidence: 99%